Phyto-Extracts in Wound Healing - Prasanta Kumar Ghosh; Anjali Gaba (Frontiers Media S.A., 2013)
Data generated through systematic investigation, carried out on the evaluation of phyto-extracts on wound healing research during the last 20 years have been compiled. About 450 plant species having wound healing properties have been identified. The present knowledge of the wound healing process comprise coagulation, inflammation, proliferation, formation and accumulation of fibrous tissues, collagen deposition, epithelialization, contraction of wound with  formation of granulation tissues, remodeling and maturation. The constituents of the plant extracts modulate one or more of the above stages. It was the endeavor to identify the active constituents responsible for antimicrobial activity, free radical scavenging properties, stimulators of enhanced collagen production and/or angiogenesis promoters with identification of lead scaffold chemical structures. Multiple phytochemicals concentrated and blended in optimal concentrations, are expected to be available in future years to carry out multi-tasking efforts in wound healing as more knowledge about the properties of the key constituents are unveiled. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.